Laboratory and Field Evaluations of Transgenic Soybean Exhibiting High-Dose Expression of a Synthetic Bacillus thuringiensis cry1A Gene for Control of Lepidoptera - Macrae, Ted C.; Baur, Matthew E.; Boethel, David J.; Gamundi, Juan Carlos; Kabuye, Victor T.; Miklos, John A.; Paradise, Mark S.; Viegas, Alejo (Journal of economic entomology, 2005)
Transgenic lines of soybean, Glycine max (L.) Merrill, expressing a synthetic cry1A gene (tic107) from Bacillus thuringiensis (Bt),were evaluated in screenhouse and conventional field trials for efficacy against lepidopteran pests. In screenhouse trials, Bt soybean and negative checks (isogenic segregants and parental lines) were evaluated against Anticarsia gemmatalis Hübner and Pseudoplusia includens (Walker) in the United States and against A. gemmatalis, Epinotia aporema (Walsingham), Rachiplusia nu (Guenée), and Spilosoma virginica (F.) in Argentina. Bt soybean exhibited virtually complete efficacy against each of these pests, whereas negative checks suffered significant damage. Bt soybean and negative checks also were evaluated in conventional trials against native populations of A. gemmatalis and P. includens in the southeastern United States. Each of these insects caused significant damage to negative checks in one or more locations, whereas Bt soybean exhibited virtually complete efficacy against these pests. In the laboratory, lyophilized leaf tissues from Bt soybean incorporated in artificial diet at a concentration representing a 25-fold dilution of fresh tissue caused complete mortality of A. gemmatalis and near complete mortality of P. includens neonates after 11 d, whereas mortality on negative checks did not exceed 10% for either insect. Average TIC107 expression approached or exceeded 50 μg/g fresh weight at V3 stage of growth and 200 μg/g by R6 stage of growth. These results demonstrate that expression of TIC107 in soybean can not only achieve highly efficacious control of several lepidopterans under field conditions but also provide a high dose for effective insect resistance management.
Keywords: Transgenic soybean; Bacillus thuringiensis; Resistance management; Lepidoptera